2001
DOI: 10.1089/108497801750096023
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Kidney Cancer with Autologous Tumor Cell Vaccines of Short-Term Cell Lines Derived from Renal Cell Carcinoma

Abstract: Vaccine therapy with short-term cultures of autologous tumor cells is feasible, well-tolerated and associated with conversion of DTH and long-term survival in patients who are free of disease at the time treatment is initiated. However, significant anti-tumor responses were not seen in patients with measurable disease at the time vaccine treatment was initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Vaccination immunotherapy was applied in patients with metastatic renal cell carcinoma before or after palliative nephrectomy and in most cases as a second or third line systemic therapy. The vaccination therapy was tested in phase I and phase II trials without control groups (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The number of patients per trial ranged between 5 and 41 patients.…”
Section: Patients For Vaccinationmentioning
confidence: 99%
“…Vaccination immunotherapy was applied in patients with metastatic renal cell carcinoma before or after palliative nephrectomy and in most cases as a second or third line systemic therapy. The vaccination therapy was tested in phase I and phase II trials without control groups (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The number of patients per trial ranged between 5 and 41 patients.…”
Section: Patients For Vaccinationmentioning
confidence: 99%
“…Compared with melanoma studies, efforts to improve outcomes for patients with RCC using GM‐CSF have been disappointing. Antitumor effects of GM‐CSF have been low, with few partial responses, although it was reported that these responses were slightly better in patients who were tumor free at the time of treatment90 and among patients who had not received prior therapy 91. In a recent Phase I trial by de Gast et al, combination therapy for patients with progressive, metastatic RCC with GM‐CSF, IL‐2, and IFN‐γ resulted in significant stimulation of effector cells and complete responses in three of eight patients 92.…”
Section: Antitumor Activity Of Gm‐csf Therapy Alonementioning
confidence: 99%
“…4,5 For several years, we have been investigating the safety and therapeutic potential of patientspecific autologous vaccines derived from shortterm autologous cell lines. [6][7][8][9][10][11][12] Theoretical advantages for the use of cells from short-term autologous tumor cell lines include: (1) the certainty that one is immunizing with antigens from the patient's own tumor, (2) an unlimited supply of tumor antigen, (3) immunization with the stem cells or progenitor cells from the tumor, (4) immunization with pure tumor cells without contamination from normal cells, (5) presentation of tumor antigens in the context of the cell membrane on metabolically active cells, (6) availability of target cells for in vitro testing of tumorspecific humoral and/or cell-mediated responses before and after vaccination, and (7) the availability of pure tumor cells for patient-specific delayed tumor hypersensitivity skin testing. Such an approach is practical for patients with metastatic melanoma, because regional recurrences and distant metastases are often in sites that are readily accessible to surgical excision, which provides an opportunity to obtain fresh tissue from which to try to establish tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] We have combined three new strategies in an effort improve on this autologous tumor cell line vaccine approach. Firstly, we, and others, have demonstrated that dendritic cells, believed to be the optimal immune cell for antigen presentation, can be derived consistently from peripheral blood mononuclear cells.…”
Section: Introductionmentioning
confidence: 99%